Industrial method of Pre-Cast Construction technologies and its break-even point study - Judson, Luke (International Journal of Engineering and Technology, 2018)
The applications of precast concrete systems have attained accelerated progress worldwide, due to several aspects, such as good quality control, speedy construction, economy, minimizing waste, pollution free, modern construction equipment and advanced concrete technologies. Due to lack of systematic understanding and awareness in the Architecture and Construction industry this method is not majorly used. In this paper describes available technologies and bringing out the advantages and benefits of these technologies by bringing out the ‘breakeven point or equal cost component’ in comparison with a traditional construction. Comparison based on specific building components, labor cost and benefits due to early completion.
Keywords: Industrial method of Pre-Cast Construction; Pre-Cast Construction of High-Rise buildings; Pre-Cast Construction.